Outpatient pulmonary rehabilitation for severe asthma with fixed airway obstruction: Comparison with COPD. (2nd December 2019) - Bellocq, Agnès; Gaspard, Wanda; Couffignal, Camille; Vigan, Marie; Guerder, Antoine; Ambard, Julien; Caruana, Sylvie; Similowski, Thomas; Garcia, Gilles; Taillé, Camille
Abstract: Background: The benefit of exercise has been demonstrated in asthma, but the role of pulmonary rehabilitation (PR) in people with severe asthma, especially with airway obstruction, has been less investigated. The activity limitation mechanisms differ in asthma and COPD, so the effect of a PR program not specific to asthma is unclear. Methods: We retrospectively compared the effect of an ambulatory PR program in nonsmoking patients with severe asthma and airway obstruction (FEV1/FVC ratio <70% and FEV1 < 80% measured twice, not under an exacerbation) and sex-, age-, FEV1-, and BMI-matched COPD controls. Results: We included 29 patients, each with asthma and COPD. Airway obstruction was moderate (median FEV1 57% [44–64]). VO2 at peak was higher for asthma than COPD patients (19.0 [15.7–22.2] vs 16.1 [15.3–19.6] ml.min −1 .kg −1, p = 0.05). After PR, asthma and COPD groups showed a significant and similar increase in constant work cycling test of 378 [114–831] s and 377 [246–702] s. Changes in Hospital Anxiety and Depression Scale (HAD) total score were similar (–2.5 [–7.0 to 0.0] vs –2.0 [–5.0 to 2.0], p > 0.05). Quality of life on the St. George's Respiratory Questionnaire (SGRQ) was significantly improved in both groups (–14.0 [–17.7 to –2.0], p < 0.005 and –8.3 [–13.0 to –3.6], p < 0.0001). Conclusion: Outpatient PR is feasible and well tolerated in patients with severe asthma with fixed airway obstruction. A nondedicated program strongly improves HAD and SGRQ scores and constant work-rate sub-maximal cycling, with similar amplitude as with COPD.